Population-based human immunodeficiency virus 1 drug resistance profiles among individuals who experienced virological failure to first-line antiretroviral therapy in Henan, China during 2010–2011 - Liu, Jia; Wu, Yasong; Yang, Wenjie; Xue, Xiujuan; Sun, Guoqing; Liu, Chunhua; Tian, Suian; Sun, Dingyong; Zhu, Qian; Wang, Zhe (AIDS research and therapy, 2015)
In Henan, China, first-line antiretroviral treatment (ART) was implemented early in a large number of treatment-experienced patients who were more likely to have a drug resistance. Therefore, we investigated the human immunodeficiency virus (HIV)-1 drug resistance profiles among patients in Henan who experienced virological failure to ART. A cross-sectional survey was administered in 10 major epidemic cities from May 2010 to October 2011. Adult patients who experienced virological failure (virus load ≥1,000 copies/mL) with >1 year of first-line antiretroviral treatment consented to provide blood for genotype resistance testing. The clinical and demographic data were obtained from the patients' medical records. Logistic regression analysis was performed to determine the factors associated with ≥1 significant drug resistance mutation. We included 3,235 patients with integral information and valid genotypic resistance data. The city, age, CD4 counts, virus load, treatment duration, and World Health Organization stage were associated with drug resistance, and 64.76% of patients acquired drug resistance. The nucleoside reverse transcriptase inhibitor (NRTI), non-(N)NRTI, and protease inhibitor resistance mutations were found in 50.26, 63.12, and 1.30% of subjects, respectively. Thymidine analogue mutations, NNRTI and even multidrug resistance complex were quite common in this patient cohort. Multiple and complex patterns of HIV-1 drug resistance mutations were identified among individuals who experienced virological failure to first-line ART in Henan, China during 2010-2011. Therefore, timely virological monitoring, therapy adjustments, and more varieties of drugs and individualized treatment should be immediately considered in this patient population.